PENGARUH KARAKTERISTIK EKSEKUTIF DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Pajrina Rizki (2021)
This study aims to analyze the effect of executive characteristics and institutional ownership on tax avoidance with corporate governance as proxied by independent commissioners as a moderating variable. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period, with a total sample of 127 companies. This research uses quantitative methods using panel data. The data analysis technique used is the classical assumption test, panel data estimation selection test, multiple linear regression test, and hypothesis testing using a significance of 5% and 10%. The results of this study indicate that: executive characteristics and institutional ownership have no effect on tax avoidance, while independent commissioners moderate the effect of executive characteristics on tax avoidance. Keywords: executive characteristics, institutional ownership, independent commissioners, tax avoidance